1972
DOI: 10.1111/j.1365-2141.1972.tb05678.x
|View full text |Cite
|
Sign up to set email alerts
|

The Anaemia of Kala Azar

Abstract: It has been confirmed that during the active phase of kala azar the erythrocyte life span is shortened. At this time patients' immunoconglutinin titres are raised, and their erythrocytes have been shown to be agglutinated by anticomplement and anti-non-y-globulin sera. Erythrocyte destruction in kala azar takes place largely in the spleen, as demonstrated by rising counts over the spleen relative to the praecordium and liver following labelling of the patients' erythrocytes with 51Cr. This point is supported b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
3

Year Published

1990
1990
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 15 publications
1
33
0
3
Order By: Relevance
“…This was also suggested by others. 11,12 Musumeci et al 13 reported similar findings in Mediterranean kala-azar. The erythrocytes were positive for direct antiglobulin tests using antisera to IgG and complement C3.…”
Section: Discussionsupporting
confidence: 66%
“…This was also suggested by others. 11,12 Musumeci et al 13 reported similar findings in Mediterranean kala-azar. The erythrocytes were positive for direct antiglobulin tests using antisera to IgG and complement C3.…”
Section: Discussionsupporting
confidence: 66%
“…Under laboratory conditions, Karle (1974) exposed erythrocytes to temperatures above the normal body temperature and found out that the osmotic fragility and permeability of erythrocytes were greatly enhanced. It was also reported that increased body temperatures decreased erythrocyte plasticity and longevity in-vivo (Woodruff et al, 1972). Consequently, temperature elevation increased the rate of immunochemical reactions thereby initiating lipid peroxidation of erythrocytes (Igbokwe, 1994).…”
Section: Anaemia Through Undulating Pyrexiamentioning
confidence: 99%
“…Various mechanisms of red cell destruction have been suggested by researchers including splenic sequestration, increased sensitivity to complement, changes in erythrocyte enzymes resulting in change in red cell membrane permeability, and presence of cold agglutinins. (14,15) Deficiencies of iron, folate and vitamin B12 may also have some additional role. (16) Studies have not shown any role of ineffective erythropoiesis in development of anemia in these patients.…”
Section: Hematological Changes Seen In Vlmentioning
confidence: 99%